Injury and illness among onshore workers in Alaska’s seafood processing industry: Analysis of workers’ compensation claims, 2014-2015 - Syron, Laura N. (Am J Ind Med, 2019)
BACKGROUND: Alaska’s onshore seafood processing industry is economically vital and hazardous. METHODS: Accepted Alaska workers’ compensation claims data from 2014–2015 were manually reviewed and coded with the Occupational Injury and Illness Classification System and associated work activity. Workforce data were utilized to calculate rates. RESULTS: 2,889 claims of nonfatal injuries/illnesses were accepted for compensation. The average annual claim rate was 63 per 1,000 workers. This was significantly higher than Alaska’s all-industry rate of 44 claims per 1,000 workers (RR=1.42, 95% CI=1.37–1.48). The most frequently occurring injuries/illnesses, were: by nature, sprains/strains/tears (993, 36%); by body part, upper limbs (1,212, 43%); and by event, contact with objects/equipment (1,020, 37%) and overexertion/bodily reaction (933, 34%). Incidents associated with seafood processing/canning/freezing (n=818) frequently involved: repetitive motion; overexertion while handling pans, fish, and buckets; and contact with fish, pans, and machinery. CONCLUSIONS: Ergonomic and safety solutions should be implemented to prevent musculoskeletal injuries/illnesses.